Appunti di metrologia mercantile genovese Un contributo della documentazione aziendale Datini - Giagnacovo, Maria (Biblioteca di storia, 2014)
This work starts from one of the most complex issues that the economic operator of the late Middle Ages had to face in order to carry out his activities, namely a constantly up-to-date understanding of the systems of weights and measures in use on the different markets, in order to rationally set their business strategies. The critical analysis of the best-known market practices and of an impressive amount of documents from the business archive of the merchant Francesco Datini from Prato (common and specialised correspondence, accounting) allowed to identify Genoa's weight system - a privileged point of view - and to compare it with the systems of other countries, which had an economic relationship with the city. Moreover, it has been possible to define the packaging used , goods by goods, with their relative weights and tares.